A map of tumor–host interactions in glioma at single-cell resolution. Issue 10 (14th October 2020) - Caruso, Francesca Pia; Garofano, Luciano; D'Angelo, Fulvio; Yu, Kai; Tang, Fuchou; Yuan, Jinzhou; Zhang, Jing; Cerulo, Luigi; Pagnotta, Stefano M; Bedognetti, Davide; Sims, Peter A; Suvà, Mario; et al.
ABSTRACT: Background: Single-cell RNA sequencing is the reference technique for characterizing the heterogeneity of the tumor microenvironment. The composition of the various cell types making up the microenvironment can significantly affect the way in which the immune system activates cancer rejection mechanisms. Understanding the cross-talk signals between immune cells and cancer cells is of fundamental importance for the identification of immuno-oncology therapeutic targets. Results: We present a novel method, single-cell Tumor–Host Interaction tool (scTHI), to identify significantly activated ligand–receptor interactions across clusters of cells from single-cell RNA sequencing data. We apply our approach to uncover the ligand–receptor interactions in glioma using 6 publicly available human glioma datasets encompassing 57, 060 gene expression profiles from 71 patients. By leveraging this large-scale collection we show that unexpected cross-talk partners are highly conserved across different datasets in the majority of the tumor samples. This suggests that shared cross-talk mechanisms exist in glioma. Conclusions: Our results provide a complete map of the active tumor–host interaction pairs in glioma that can be therapeutically exploited to reduce the immunosuppressive action of the microenvironment in brain tumor.